1993
DOI: 10.1002/cber.19931260617
|View full text |Cite
|
Sign up to set email alerts
|

Organosubstituierte 1,1′‐Spirobisilole und 1,1′‐Spirobigermole durch vierfache Organoborierung von Tetra‐1‐alkinylsilanen und ‐germanen

Abstract: 5f, 5g, 6f, 8f, 9g, log, l l g ) of which only 9 g (R = Ph) corresponds to the spirosilanes and -germanes. This is the result of effective competition between intramolecular and intermolecular organoboration in the case of the tetra-1-alkynyltin compounds. The protodeborylation of l a , b and 2d, e with MeCOzH leads to 12a, b and 13d, e, respectively. 12a isomerises by UV irradiation to ally1 isomers 12a'. From 12a with 2 equiv. of maleic anhydride the 1:2 addition compound 14a is obtained, the autaddition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…3b, which are consistent with carbons in six different environments within the molecule. 12 These spectra are in agreement with the previous results measured on the phenylacetylene-capped SiNPs. 1 The ALC resonances that are observed are around 2.2 T for both the compound and the nanoparticle samples (see Fig.…”
Section: Resultssupporting
confidence: 92%
“…3b, which are consistent with carbons in six different environments within the molecule. 12 These spectra are in agreement with the previous results measured on the phenylacetylene-capped SiNPs. 1 The ALC resonances that are observed are around 2.2 T for both the compound and the nanoparticle samples (see Fig.…”
Section: Resultssupporting
confidence: 92%
“…which has been partly analyzed [51]. Although stannoles are present in this mixture, they could not be isolated in pure state.…”
Section: Stannacyclopentadienes: 11-organoboration Ofmentioning
confidence: 98%
“…Both dialkyn-1-yl(diorgano)germanium, Me 2 Ge(C C-R 1 ) 2 , and tetraalkyn-1-ylgermanium compounds, Ge(C C R 1 ) 4 , have been studied in their reactivity toward triethylborane [51]. This has led to the germoles 33 [7,55] and spirogermanium compounds (1,1 -spirobigermoles) 34 [51] (Scheme 17). In the case of Me 2 Ge(C C R 1 ) 2 the germole 33 was also obtained for R 1 = OMe [56].…”
Section: Germacyclopentadienesmentioning
confidence: 99%
“…In addition to numerous saturated spirosilanes and a few examples of 5-silaspiro[4,4]nona-2,7-dienes, [3,4] previous work has shown that ethylboration of tetraalkyn-1-ylsilanes, Si(CϵC-R) 4 , provides a straightforward route to 1,1-spirobisiloles A. [5][6][7] Recently, we characterized the first spirosilanes containing two four-membered rings B by using 1,2-hydroboration and 1,1-organoboration. [8] The combination of these stereo-and regioselective reactions is attractive in synthesis, [8][9][10] and in the present work further examples are given that are aimed at the synthesis and first structural characterization of the hitherto unknown 5-silaspiro[4,4]nona-1,6-diene derivatives.…”
Section: Introductionmentioning
confidence: 99%